2018
DOI: 10.1038/s41467-018-06474-w
|View full text |Cite
|
Sign up to set email alerts
|

Interface dominated cooperative nanoprecipitation in interstitial alloys

Abstract: Steels belong to one of the best established materials, however, the mechanisms of various phase transformations down to the nano length scale are still not fully clear. In this work, high-resolution transmission electron microscopy is combined with atomistic simulations to study the nanoscale carbide precipitation in a Fe–Cr–C alloy. We identify a cooperative growth mechanism that connects host lattice reconstruction and interstitial segregation at the growing interface front, which leads to a preferential gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 34 publications
1
6
0
Order By: Relevance
“…During the structural transformation from matrix to precipitates, the kinetics and the morphology of the precipitates may be dominated by the energetics of the involved interfaces between the precipitates and the confining matrix. This has been demonstrated in a recent study 328 of Fe 3 C precipitation in the well-established Fe-C system [Fig. 28(a)].…”
Section: Morphology Of Nanoprecipitatessupporting
confidence: 66%
See 1 more Smart Citation
“…During the structural transformation from matrix to precipitates, the kinetics and the morphology of the precipitates may be dominated by the energetics of the involved interfaces between the precipitates and the confining matrix. This has been demonstrated in a recent study 328 of Fe 3 C precipitation in the well-established Fe-C system [Fig. 28(a)].…”
Section: Morphology Of Nanoprecipitatessupporting
confidence: 66%
“…% C. By evaluating the MEP of C migration to interface I using NEB calculations (see Sec. III A 2), Wang et al 328 identified a thermodynamic driving force for C to diffuse from the ferrite matrix to the advancing interface [Fig. 28(c)].…”
Section: Morphology Of Nanoprecipitatesmentioning
confidence: 99%
“…However, this is beyond the scope of the current work. Details regarding this aspect of the microstructural evolution can be found elsewhere [28,[39][40][41]. e A HRTEM micrograph of a h particle in the WQ specimen.…”
Section: Microstructural Features Observed By Semmentioning
confidence: 99%
“…In recent years, outside of the field of battery materials research, it has been reported that over-stoichiometric cations may locate at interstitial sites in various types of fcc lattices, [37][38][39][40][41][42] hinting at the possibility of over-stoichiometric chemical spaces for rock salt structures. Moreover, a number of pioneering works have indicated that interstitial sites (e.g., tetrahedral sites) in the fcc-or near-fcc-type cathodes may be occupied by cations, which also suggests that rock salt structures may host extra cations.…”
Section: Introductionmentioning
confidence: 99%